Rural consumers’ attitude towards khadi products - Padmasani; S, Muruganandan; M, Yazhini (Journal of Management and Science, 2011)
In this study the consumers‟ attitude towards khadi products is reviewed through Fishbein‟s attitude model. The influence of personal characteristics and purchase preference factors on the attitude as well as the association between attitude and consumer‟s satisfaction are examined. This study shows that, overall, the consumers have positive attitude towards khadi product and also that the consumers who have higher attitude get more satisfaction.